2018
DOI: 10.1021/acs.jpclett.8b02229
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Rate-Limiting Li-Ion Diffusion Pathway in Ultrathick Electrodes for Li-Ion Batteries

Abstract: Increasing the loading of active materials by thickening the battery electrode coating can enhance the energy density of a Li-ion cell, but the trade-off is the much reduced Li transport kinetics. To reach the optimum energy and power density for thick electrodes, the effective chemical diffusion coefficient of Li ( D) must be maximized. However, the diffusion of Li inside an electrode is a complex process involving both microscopic and macroscopic processes. Fundamental understandings are needed on the rate-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(116 citation statements)
references
References 35 publications
3
113
0
Order By: Relevance
“…Therefore, from the present results and those published in literature, it is reasonable to conclude that electrodes with thickness less than the ion diffusion coefficient (< 20 nm) support PC charge storage. This idea of morphology driven pseudocapacitance in thin materials structures could be drawn from the fundamental mechanism governing the charge storage in electrochemical cells [3] as well as by recently published literatures [31][32][33][34]. Fundamentally, the extend of charge diffusion in the electrode differentiates batteries and pseudocapacitors despite their similar faradaic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, from the present results and those published in literature, it is reasonable to conclude that electrodes with thickness less than the ion diffusion coefficient (< 20 nm) support PC charge storage. This idea of morphology driven pseudocapacitance in thin materials structures could be drawn from the fundamental mechanism governing the charge storage in electrochemical cells [3] as well as by recently published literatures [31][32][33][34]. Fundamentally, the extend of charge diffusion in the electrode differentiates batteries and pseudocapacitors despite their similar faradaic processes.…”
Section: Resultsmentioning
confidence: 99%
“…Although, increasing the electrode thickness significantly enhances the specific capacity of the electrode up to approximately 100 µm, theoretical [19,[29][30][31][32][33][34] and experimental [35][36][37][38] results clearly show that large electrode thicknesses lead to low rate capability originating from Li + diffusion limitations in the electrolyte. For example, the conductive additive content can be increased until limitations of the electron transport in the composite become negligible.…”
mentioning
confidence: 95%
“…In contrast to that, the electrode thickness and the specific capacity of the active material cannot be optimized regarding the rate performance without affecting the energy density. Although, increasing the electrode thickness significantly enhances the specific capacity of the electrode up to approximately 100 µm, theoretical [19,[29][30][31][32][33][34] and experimental [35][36][37][38] results clearly show that large electrode thicknesses lead to low rate capability originating from Li + diffusion limitations in the electrolyte. Similarly, increasing the gravimetric capacity of the active material enhances the specific capacity of the electrode, but the larger current density at a given C-rate also leads to increased Li + diffusion limitations in the electrolyte and a corresponding decline in capacity at higher rates.…”
mentioning
confidence: 99%
“…Patry et al evaluated the impact of electrode coating thickness on the cell cost for different cathode active materials (AMs) and found that the doubling of the electrode thickness from 50 to 100 μm for NCM 111 (Li(Ni 1/3 Co 1/3 Mn 1/3 )O 2 ) leads to a potential cost reduction of 24% per kilowatt hour ($ kW h −1 ) . Therefore, the concept of thick electrodes was recently investigated experimentally by several groups, yielding electrodes with high mass loadings, for example, coated on porous metal current collectors or produced binder‐free by Templating or Spark Plasma Sintering (SPS) and studied by modeling and simulation …”
Section: Introductionmentioning
confidence: 99%
“…During the fabrication of thick electrodes, special treatment concerning mixing, drying, and handling becomes necessary to yield mechanically stable electrodes. With regard to the electrochemical performance, thick electrodes suffer from mass transport limitations of lithium ions in the electrolyte phase and an increasing impedance for electrons in the solid phase of the electrode . Recent literature used theoretical approaches to prove that electrochemical reactions in porous electrodes under high current densities are limited by liquid‐phase transport mechanisms attributed to a concentration gradient and resulting electrolyte depletion.…”
Section: Introductionmentioning
confidence: 99%